Spatial Analysis On Strong Winds Occurrence In The Northern Regionmalaysia Based On Interpolated Wind Speed And Wind Direction Map - Taufik, Ruzainah Ahmad (Universiti Sains Malaysia, 2017)
This final year research project reviews the problem on the characteristics of the strong winds occurrence in the northern region Malaysia. The specific month i.e. October 2014 was selected that coincides with the period where the tornado outbreak was reported to damage properties in Pendang district, Kedah. The study was intended to determine the effect of the wind speed and wind direction on that specific month that contributes to the strong wind occurrences. The wind data collected were processed and spatially interpolated to produce wind speed and wind direction map using GIS-IDRISI software. From the map analysis, the highest wind speed recorded was 3.1 m/s on the 4th October 2014 at Butterworth meteorological station. Meanwhile, Pulau Langkawi and Chuping stations have recorded the calmest wind speed of 0.3 m/s on 10th October and 23rd October respectively. The plotted wind speed and wind direction maps were able to show clearly the territory of the wind blows, where directions are shown by arrows and the wind velocity represented by continuous colours. The results have also produced contoured wind map within the northern region Malaysia. The spatial statistics determines the relationship of wind speed and wind direction and the results were illustrated using line charts, raster wind speed maps and the wind rose diagram represents the wind direction. The outcomes of the study are essential in showing the importance of wind speed and direction parameters in the design of building structures that consider resistance to intense wind.